2016
DOI: 10.1111/add.13198
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement uniquely predicts reductions in alcohol‐impaired crash fatalities

Abstract: Drunk driving enforcement intensity uniquely contributes to reductions in alcohol-impaired crash fatalities after controlling for other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
1
25
2
Order By: Relevance
“…Further, in the present study, places with more city DUI arrests per population, there were proportionally fewer DUI injury/fatal crashes. While this is cross-sectional, this association is consistent with other research (Yao et al 2016) and the decreased self-reported driving behavior among those most likely to drink outside the home.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Further, in the present study, places with more city DUI arrests per population, there were proportionally fewer DUI injury/fatal crashes. While this is cross-sectional, this association is consistent with other research (Yao et al 2016) and the decreased self-reported driving behavior among those most likely to drink outside the home.…”
Section: Discussionsupporting
confidence: 91%
“…In the U.S., detection of drinking and driving is low (Yao et al 2016; Voas and Fell 2016). An estimated 1.4 million drivers are arrested for driving while intoxicated (DWI) or driving under the influence (DUI) each year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a nationally representative study, Fell et al [3] found that a 10% increase in the DWI arrest rate per capita in a community was associated with a 1% decrease in alcohol-impaired driving crashes in that locality. Using a 11-year sample (1996-2006) of state data from the Fatality Analysis Reporting System, Yao et al [4]-in a paper in this issue-studied states with increases and decreases in the percentage of alcohol-impaired fatal crashes during that 11-year period and found that states that had higher DWI arrest rates per capita had reductions in the percentage of fatal crashes involving an alcohol-impaired driver.…”
Section: Relationship Of Arrests To Impaired Driving Crashesmentioning
confidence: 99%